Finite element analysis of composite sandwich beams in 3-point bend test - Ong, Nykson Lee Shen (Nanyang Technological University, 2023)
This project reports the findings of using ANSYS as the Finite Element Analysis (FEA) software in simulating isotropic unifoam beams and composite sandwich beams subjected to a 3-Point Bend Test. The version of ANSYS used was ANSYS 2022 R2 (Student) which has a limitation of 32,000 nodes.